In vitro anti-cancer and antimicrobial effects of manganese oxide nanoparticles synthesized using Glycyrrhiza uralensis leaves extract on breast cancer cell lines - Althobiti, Maryam Musleh; Alzahrani, Badr; Elderdery, Abozer Y.; Alzerwi, Nasser A. N.; Rayzah, Musaed; Elkhalifa,, Ahmed M. E.; Idrees, Bandar; Bakhsh, Ebtisam; Alabdulsalam, Abdulrahim A.; Mohamedain, A.; Kumar, Suresh S.; Mok, Pooi Ling (Walter De Gruyter, 2023)
In this study, we evaluated the antiproliferative and apoptotic properties of Pluronic-F127-containing manganese oxide nanoparticles (PF-127-coated Mn2O3 NPs) derived from the leaf extract of Glycyrrhiza uralensis (GU) on breast adenocarcinoma, MCF7, and MDA-MB-231 cell lines. The leaf extract of GU contains bioactive molecules that act as a reducing or capping agent to form Mn2O3 NPs. Various analytical techniques were used to characterize the physiochemical properties of PF-127-coated Mn2O3 NPs, including spectroscopy (ultralight-Vis, Fourier transform infrared, photoluminescence), electron microscopy (field emission scanning electron microscopy and transmission electron microscopy), X-ray diffraction (XRD), electron diffracted X-ray spectroscopy (EDAX), and dynamic light scattering. The average crystallite size of Mn2O3 NPs was estimated to be 80 nm, and the NPs had a cubic crystalline structure. PF127-encapsulated Mn2O3 NPs significantly reduce MDA-MB-231 and MCF-7 cell proliferation, while increasing endogenous ROS and lowering mitochondrial matrix protein levels. DAPI, EtBr/AO dual staining, and Annexin-V-FITC-based flow cytometry analysis revealed that PF127-coated Mn2O3 NP-treated breast cancer cells exhibit nuclear damage and apoptotic cell death, resulting in cell cycle arrest in the S phase. Furthermore, PF127-encapsulated Mn2O3 NPs show strong antimicrobial efficacy against various strains. As a result, we can conclude that PF127-coated Mn2O3 NPs may be effective as future anticancer agents and treatment options for breast cancer.